Phanerogamae Species in The Post-Liquefaction Area of Balaroa Subdistrict, Palu City - Gina Rizkyta Aulia; Astija Astija; Hayyatun Mawaddah; Lestari M.P. Alibasyah; Aan Febriawan; Musdalifah Nurdin (Biology, Medicine, & Natural Product Chemistry, 2026)
Phanerogamae are classified as plants with the highest level of phylogenetic development because they produce seeds. Ontogenetically, seeds function as the generative reproductive structures of these plants, as their formation is preceded by sexual reproduction. This study aimed to identify and describe the morphological characteristics of Phanerogamae plants in the post-liquefaction area of Balaroa Subdistrict, Palu City. The research was motivated by the limited scientific information regarding plant species capable of growing and adapting to post-liquefaction environments. A descriptive-exploratory method was employed through direct field observations and morphological identification based on root, stem, leaf, flower, fruit, and seed characteristics. The results revealed the presence of 22 Phanerogamae species belonging to two classes and twelve orders, exhibiting diverse morphological characteristics and varying patterns of vegetation distribution. Several species were found to dominate specific areas according to habitat conditions, such as waterlogged zones and open lands formed after the disaster. The study concludes that the post-liquefaction area of Balaroa Subdistrict continues to support the growth of various Phanerogamae species that possess the capacity to adapt to environmental changes.